Fundamentals of Entrepreneurship (ENT300) : Bubble scrub car wash / Nurfarahin Hamzaini ... [et al.] - Hamzaini, Nurfarahin; Wahid, Nurhisyam; Shazali, Mohammad Dzulkarnain; Nizam, Aiman Rasyid; Abdul Rahman, Khairul Ikhwan (2014)
Our company name is Bubble Scrub Carwash This business has been decided on a form of partnership, which consists of five members. Each member will contributes certain amount of capital for the success of this carwash We also decided that our business will operate at Petra Jaya, commercial centre, Kuching, Sarawak and fully operate on the I st of January 2015 .Our main business activity is to provide a convenient service to the residence around Petra Jaya, commercial center with our wide range of offered services to the customers. The aim for this company is to create a good carwash services experience for Indlviduals which also includes a good customer service when handling the customers car with handle and care All the partners are encouraged and entitled to provide their full time commitment to the services in the business management. We have agreed that Nurfarahin Binti Hamzaini will be the General Manager, Aiman-Rasyid Bin Nizam will be the Administrative Manager, while Nurhisyam Bin Wahid will be our Marketing Manager, Mohd Dzulkarnain Bin Shazali will be our Operation Manager, and Khairul Ikhwan Bin Abdul Rahman has been appointed as our Financial Manager.